Rancang Bangun dan Pengujian Aplikasi Bank Soal Interaktif Berbasis Android Menggunakan V-Model - Hadi ihmaludin; Tedi Budiman (Masoem University, 2026)
The development of information technology has encouraged the use of mobile devices as supporting media in learning processes, including student assessment activities. However, evaluation in Information Technology subjects is still commonly conducted conventionally, resulting in limited interactivity and inefficiency in question management. This study aims to design and test an interactive question bank application based on Android using the V-Model as the software development methodology. This research employs a Research and Development (R&D) approach with V-Model stages consisting of requirement analysis, system design, architectural design, implementation, and testing phases including unit testing, integration testing, system testing, and user acceptance testing. Usability testing was conducted using the System Usability Scale (SUS) to measure the feasibility level of the application. The results indicate that all system functions operate according to the specified requirements and achieve a good category based on user evaluation. Therefore, the developed application is considered feasible to be used as an interactive and effective learning evaluation media.